Penyuluhan Hukum Islam melalui Media Edukasi Fikih Ramadhan sebagai Upaya Meningkatkan Kualitas Ibadah Masyarakat - Farida Arianti; Desi Yusdian; Elvy Rahmi Mawarnis; Ahmad Salman Farid (Karsa : Jurnal Pengabdian Masyarakat, 2026)
This Community Service (PKM) activity aimed to enhance public understanding of Fiqh of Ramadan as an integral part of Islamic law and to improve the quality of worship through educational outreach delivered online via the Zoom Meeting platform. The PKM employed the Participatory Action Research (PAR) method with an educational-participatory approach that actively involved participants throughout all stages of the program, including needs assessment, interactive educational sessions, discussion and question-and-answer activities, and evaluation of participants' understanding through Google Forms-based pretests and posttests. The educational media utilized included visual presentations, infographics, and short videos explaining various aspects of Ramadan fiqh, such as fasting regulations, recommended acts of worship, zakat al-fitr, and contemporary fiqh issues frequently encountered by the community. The program was attended by 65 participants from diverse age groups and professional backgrounds. The evaluation results indicated a significant improvement in participants' average understanding scores, increasing from 64.3 in the pretest to 88.7 in the posttest. In addition to cognitive improvement, participants demonstrated a high level of engagement during the discussion sessions, as reflected in their enhanced ability to identify and resolve Ramadan fiqh issues based on authentic sources of Islamic law. The findings demonstrate that educational outreach through Zoom-based learning media is an effective alternative for implementing community service programs, as it can reach participants regardless of geographical limitations, foster interactive learning, and strengthen public religious literacy. Therefore, this online educational outreach model is recommended as an adaptive community engagement strategy that aligns with advances in information technology while supporting the improvement of the quality of worship within the community.